BRASH Syndrome: A Patient With Chronic Kidney Disease and AV Nodal Blockers - Zein A Alsayed-Ahmad; Sanaa Saddour; Tasnim Mustafa Saddour; Mohamad Moafak Hariri; Karam Albitar; Sami Albitar (Case Reports in Nephrology)
Conclusions: BRASH syndrome is a serious complication of hyperkalemia, hypotension, and bradycardia in patients with kidney dysfunction and AV-blocking medications. It may require hemodynamic support and temporary pacemaker insertion. Early recognition and treatment of this entity can reduce mortality and morbidity.